Пошаговое объяснение:
x+3/7=19/21
x=19/21-3/7 приводим к общему знаменателю
x=19/21-9/21
x=10/21
11/16+х=7/8
х=7/8-11/16 приводим к общему знаменателю
х=14/16-11/16
х=3/16
х-2/19 = 13/57
х = 13/57+2/19 приводим к общему знаменателю
х = 13/57+6/57
х = 19/57 сокращаем на 19
х = 1/3
Х+3/7=19/21
Х=19/21-3/7
Х=19/21-9/21
Х=10/21
11/16+Х=7/8
Х=7/8-11/16
Х=14/16-11/16
Х=3/16
Х-2/19=13/57
Х=13/57+2/19
Х=13/57+6/57
Х=19/57=1/3
Пошаговое объяснение:
x+3/7=19/21
x=19/21-3/7 приводим к общему знаменателю
x=19/21-9/21
x=10/21
11/16+х=7/8
х=7/8-11/16 приводим к общему знаменателю
х=14/16-11/16
х=3/16
х-2/19 = 13/57
х = 13/57+2/19 приводим к общему знаменателю
х = 13/57+6/57
х = 19/57 сокращаем на 19
х = 1/3
Х+3/7=19/21
Х=19/21-3/7
Х=19/21-9/21
Х=10/21
11/16+Х=7/8
Х=7/8-11/16
Х=14/16-11/16
Х=3/16
Х-2/19=13/57
Х=13/57+2/19
Х=13/57+6/57
Х=19/57=1/3
Пошаговое объяснение: